Extinction of presidential immunity for cases of corruption in the Political Constitution of Peru of 1993 - Roel Alva, Luis Andrés; Oblitas Villalobos, William Jesús (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
The purpose of this paper is to analyse whether the cause of corruption can be incorporated as an additional exception to presidential immunity in the 1993 Constitution; and, together with this, it is proposed to regulate this cause as a constitutional infringement. The method used in this research is explanatory, where the cause-effect relationship between the corruption variable and the languishing of the democratic system will be established, making use of philosophy, constitutional doctrine, the Constitutional Court and the position of the UN (expressed through its conventions), with respect to the social gravity that radiates from this scourge, and the need to protect the model and the fundamental rights that it harbours.In view of the aforementioned sources and considering that the higher the function, the greater the responsibility, it is imperative to amend article 117 of the Constitution, which regulates presidential immunity. In this way, it is necessary to specify that it is also possible to accuse the president of the Republic in cases of corruption, understanding this as a crime or as a constitutional infraction; being that both in their procedure would be executed under consonance with due process.
Keywords: presidential immunity; corruption; constitutional infringement; international treaties